The Impact of Chronic Electronic Cigarette Use on Alveolar Macrophage Lipid Content: Case Report - Ruttenberg, Molly; Armstrong, David; Mellinger, Diane; Carroll, James; Ashare, Alix (Archives of Clinical and Medical Case Reports, 2022)
Background: While acute respiratory distress following electronic cigarette (e-cig) use has been described, the effects of chronic e-cig use on lung health are currently unknown. Acute e-cigarette/vaping product useassociated lung injury (EVALI) has been highlighted recently in numerous cases across the United States. Numerous EVALI case reports highlight alterations in alveolar macrophages, justifying investigation of this key immune sentinel of the lung in habitual e-cig users. Case Presentation: After informed consent, we performed a bronchoscopy on a 25 year asymptomatic woman who reported daily e-cig use. To evaluate for evidence of abnormal lipid homeostasis, we performed histologic and Oil Red O stain evaluation of alveolar macrophages obtained from bronchoalveolar lavage fluid. Our analyses demonstrate a prevalence of cells with high lipid accumulation in multiple, discrete cytoplasmic foci. We found a high lipid laden macrophage index within alveolar macrophages isolated from a chronic e-cig user. At the ultrastructural level, we found membrane-bound compartments filled with material of various densities segregated along curved phase separation lines reminiscent of suspensions of immiscible fluids. Conclusions: We found a unique ultrastructural pattern in alveolar macrophages isolated from a chronic e-cig user that is unlike any other previously reported in aspiration syndromes and may represent a defining diagnostic feature of chronic e-cig use.